Prediction the results of ablative treatment in patients with uveal melanoma using molecular markers of lymphocyte activation (Ukrainian Journal of Ophthalmology, 2026)
Abstract. One approach to predicting the outcome of ablative treatment is the study of the expression of molecular markers of lymphocyte activation. Changing the level of expression of receptors on the cell surface reflects the processes in the body. The purpose — to explore the possibility of predicting the results of ablative treatment using molecular markers of lymphocyte activation.A comparative analysis of the expression of lymphocyte activation molecular markers was made in 150 patients with uveal melanoma. The expression level of molecular markers of lymphocyte activation CD54+ and CD95+ was studied using monoclonal antibodies by histoimunocytochemical method on peripheral blood lymphocytes. I group (116 patients) — patients with uveal melanoma regression after photocoagulation and ?-therapy; II group (34 patients) — patients with progressive tumor growth and subsequent removal of the eye.The study evaluated informative predictability of lymphocyte activation molecular markers CD54+ and CD95+ to assess possible to determine the level of markers for predicting success of ablative treatment. ROC-analysis (Receiver Operating Characteristic analysis) showed that molecular markers of lymphocyte activation CD54+ and CD95+ were the most informative. Thresholds expression level was defined on peripheral blood lymphocytes CD54+ (above 171 cells/ml — absolute level) and CD95+ (above 282 cells/ml — absolute level); CD54+ (above 19% — relative level) and CD95+ (above 18% — relative level), predicts regression of melanoma in 77,2% of cases. Expression lymphocyte activathion molecular markers CD54+ and CD95+ below this level allows to predict subsequent tumor growth in 70,5% of cases.
Keywords: uveal melanoma; molecular markers of lymphocyte activation; prediction result of treatment